2021
DOI: 10.1038/s41598-021-85124-6
|View full text |Cite
|
Sign up to set email alerts
|

Green propolis extract attenuates acute kidney injury and lung injury in a rat model of sepsis

Abstract: Sepsis is the leading cause of acute kidney injury (AKI) and lung injury worldwide. Despite therapeutic advances, sepsis continues to be associated with high mortality. Because Brazilian green propolis (GP) has promising anti-inflammatory, antioxidant, and immunomodulatory properties, we hypothesized that it would protect kidneys and lungs in rats induced to sepsis by cecal ligation and puncture (CLP). Male Wistar rats were divided into groups—control (sham-operated); CLP (CLP only); and CLP + GP (CLP and trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 40 publications
2
21
0
Order By: Relevance
“…Most intensive care unit patients will die from multiple rather than individual organ failure (Vincent, 2011). Sepsis is the leading cause of both AKI and ALI, and sepsis is characterized by systemic inflammation caused by infection (Yanet al , 2019;Silveira et al , 2021). LPS as a potent inducer of excessive inflammatory response, is widely used to establish AKI and ALI mouse models, which exhibit similar pathological changes to those found in human infectious sepsis (Ju et al , 2018;Islam et al , 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most intensive care unit patients will die from multiple rather than individual organ failure (Vincent, 2011). Sepsis is the leading cause of both AKI and ALI, and sepsis is characterized by systemic inflammation caused by infection (Yanet al , 2019;Silveira et al , 2021). LPS as a potent inducer of excessive inflammatory response, is widely used to establish AKI and ALI mouse models, which exhibit similar pathological changes to those found in human infectious sepsis (Ju et al , 2018;Islam et al , 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological analysis has shown that sepsis is common pathology of AKI and ALI patients (Silveira et al , 2021). Sepsis is manifested by systemic inflammation, leading to multiple organs dysfunction, and the kidneys and lungs are the most vulnerable organs (Ibrahim et al , 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compounds derived from green propolis negatively regulate the expression of TMPRSS2 and the anchoring of ACE2, which limits entry of the virus [10,11]. Additionally, these compounds promote the immunomodulation of NF-κB, the NLRP3 in ammasome and monocytes/macrophages, reducing the overproduction of proin ammatory cytokines [1,6,7]. Experimental evidence also points to propolis substances capable of reducing activation of the PAK1 pathway, an important target used by the virus to shield itself from adaptive immunity [12].…”
Section: Propolis: Experimental Evidence Against Viral Targetsmentioning
confidence: 99%
“…Propolis is a natural resin with considerable evidence of antioxidant, antiviral, antiproteinuric, immunoregulatory and anti-in ammatory activities, and experimental data point to its potential actions against viral targets [1,[5][6][7].…”
Section: Introductionmentioning
confidence: 99%